Hypoglycemic effect of Gymnema sylvestre (retz.,) R.Br leaf in normal and alloxan induced diabetic rats - Sathya, S. (Medknow Publications & Media Pvt Ltd, 2008)
The water extract of Gymnema sylvestre R.Br leaf was tested for hypoglycemic activity in normal and alloxan induced diabetic rats. Grated amount (2ml/kg) of the water extract of Gymnema sylvestre leaf was given to both normal and alloxan induced diabetic rats. A significant reduction of glucose concentration was noticed in normal rats, blood glucose level was significantly reduced in diabetic rats. Protein level is also decreased in diabetic rats. Urea, uric acid and creatinine levels were increased in diabetic condition. After the herbal treatment the levels were altered near to normal level.